Avaliação da sustentabilidade econômica, ambiental e social na criação do camarão marinho Litopenaeus vannamei em diferentes estratégias de manejo - Bessa Júnior, Ambrosio Paula (Universidade Federal Rural do Semi-Árido, 2017)
Aquaculture studies seem to be basically based on environmental and economic terms in isolation, not considering the interaction of these factors, and rarely taking into account the social costs and benefits involved in the activity, so the objective of this research was to evaluate sustainability economic, environmental and social aspects in the creation of Litopenaeus vannamei shrimp in different management strategies and storage densities. For this purpose, densities of 92 (M1), 14 (M2) and 8 (M3) shrimp.m-2 and with maximum culture time of 79 days. The sedimentation rates, with the exception of total inorganic carbon-TIC and total organic carbon-TOC, were significantly higher in M3 when compared to M1 and M2, in the first collection period, probably influenced by management in the first stage (greenhouse), a tendency of decrease was verified for most of nutrient sedimentation rates for the end of the cycle, and may be associated with the bacterial community that may have aided in the reduction of these compounds. Survival was reduced in all treatments, probably influenced by white spot disease and high water salinity of farms raising the apparent feed conversion factor-FCAA in M1 and M2. The internal rates of return for M2 and M3 were attractive, generating a positive net profit and a positive balance and were able to guarantee the return on invested capital. However, this return on capital only occurred due to the high prices practiced in 2016. The cultivation with high initial population (M1) caused economic and zootechnical losses due to the high FCAAs, reduced individual biomass and the high total operational costs - making this treatment unfeasible. In the social evaluation, an income distribution of the negative order for M1 was verified due to the high costs of production, thus creating losses for this treatment. M2 and M3 presented a reduced income distribution, with a labor compensation of R $ 0.70 and R $ 1.06, respectively, representing 48 and 32% of production costs (COT). The greater distance from the economic dimension to the M1 treatment may be associated with the high RB and COT results. The treatments M2 and M3 were those that presented positive IRR, demonstrating the economic viability, probably due to the high prices per kilo of shrimp practiced during this period. Sustainability was committed by the generation of solid waste, since much of the particulate matter produced in shrimp farms is formed by a collective action of chemicals, fertilizers, excrement, undigested food, unwanted organisms and debris. It is worth noting that the white spot negatively affected the economic and social sustainability of all treatments. M1 was the most favorable environmental treatment with a social tendency. We can conclude that the monoculture of shrimp when carried out with high initial populations can not guarantee the return of invested capital. M2 and M3 were only economically viable due to the high prices paid per kilo of shrimp, but with low employment and income generation, not being socially fair and with greater impact on the environment
Evaluation of economic, environmental and social sustainability in the creation of marine shrimp Litopenaeus vannamei in different management strategies
Keywords: Camarão; Indicadores; Mancha Branca; Sustentabilidade; Taxas de sedimentação; Indicators; Sedimentation rates; Shrimp; Sustainability; White spot; CIENCIAS AGRARIAS::MEDICINA VETERINARIA